Examining Performance Determinants of Commercial Banks: Evidence from the Tanzanian Banking Sector - Mulbah, Kessellie Traore; Kurbonov, Sinbad; Nasriddinov, Bobur (European Scientific Journal, ESJ, 2024)
While the current body of literature offers valuable insights into the factors influencing bank financial performance, there remains a significant paucity of empirical research focusing on least developed nations. In this paper, we present new evidence of the effect of bank size, capital adequacy ratio (CAR), and net interest margin (NIM) on commercial banks’ performance (return on assets (ROA)) from the perspective of Tanzania – a least-developed country. We employed the Random Effect, and the Generalized Least Squares (GLS) regression models utilizing a panel dataset spanning the period 2000 to 2022 of ten (10) Tanzanian commercial banks to examine the specific effect of the foregoing variables on commercial banks’ profitability. These banks have a combined share of approximately 85 percent of the total assets (TZS 46 trillion) of the Tanzanian banking sector. We found that capital adequacy and bank size have positive significant effects on the financial performance of commercial banks in Tanzania. Whereas the random effect model shows a marginally significant positive effect on ROA, the GLS regression shows a significant negative effect, indicating that the effect of NIM could be either positive or negative depending on the context. Thus, we intimate that regulators prioritize measures aimed at promoting healthy levels of capital adequacy and encouraging the growth of larger banks while ensuring adequate oversight to mitigate potential risks associated with market dominance, and regulatory frameworks should be designed to foster competition and efficiency in the banking sector, facilitating a conducive environment for banks of all sizes to thrive.